IMPLEMENTATION OF MIND MAPPING-BASED DISCOVERY LEARNING MODEL IN ONLINE LEARNING ON COLLOID MATERIALS - Mahdian Mahdian; Rilia Iriani; Leny Leny; Rinda Oktavia Novianti (Universitas Lambung Mangkurat, 2024)
Research has been conducted on the implementation of the discovery learning model based on mind mapping in online learning on colloid materials. This study aims to determine the difference in knowledge learning outcomes, attitudes, and student responses to the discovery learning model based on mind mapping in online learning on colloid materials. The method used is a quasi-experiment using a